2017
DOI: 10.5005/jp-journals-10024-1999
|View full text |Cite
|
Sign up to set email alerts
|

Most Frequent Oral Lesions in Patients with Type 2 Diabetes Mellitus

Abstract: Aim: Type 2 diabetes mellitus (DM2) is a chronic disease caused by the underproduction of insulin in the organism and it is considered a risk factor to periodontal disease. Materials and methods:This study performed a cross-sectional research on the main oral changes in patients with DM2 and nondiabetics, in Passo Fundo, Rio Grande do Sul, Brazil. The sample included 116 patients examined at the Diabetes Outpatient Clinic of the School of Medicine of the University of Passo Fundo (UPF) and 134 nondiabetic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…7 Oral pathology is one of the major complications in DM2 patients and, therefore, it is important to intervene early in order to reduce the risk of a future interaction between these pathologies. [8][9][10][11] The emphasis on similarities between determinants of OH and GH is broadly consistent and leads to the conclusion that OH is an integral part of GH. 12 Some studies have identified associations between oral pathology and DM2, 1,8,13,14 and both are associated with a worse perceived GH 15 and worse oralhealth quality of life due to OH manifestations.…”
Section: Introductionmentioning
confidence: 88%
“…7 Oral pathology is one of the major complications in DM2 patients and, therefore, it is important to intervene early in order to reduce the risk of a future interaction between these pathologies. [8][9][10][11] The emphasis on similarities between determinants of OH and GH is broadly consistent and leads to the conclusion that OH is an integral part of GH. 12 Some studies have identified associations between oral pathology and DM2, 1,8,13,14 and both are associated with a worse perceived GH 15 and worse oralhealth quality of life due to OH manifestations.…”
Section: Introductionmentioning
confidence: 88%
“…The methodological analysis of the included articles is presented in Table 3. Six articles were classified as cross-sectional studies 12,28,29,30,31,32 and one was classified as a cohort study. 11 This study 11 was included because the results on oral candidiasis were shown as cross-sectional data.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Concerning the sample matching, three studies 11,12,30 did not match the samples with sample size, which we considered as a minor problem (+). Moreover, two studies 28,32 did not match the samples with respect to the gender and age of the participants, which was considered a major problem (++).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Стан гігі-єни порожнини рота у пацієнтів з ЦД в 2,5 рази гірший, ніж у здорових осіб. Для таких пацієнтів характерні подовжені строки загоєння ран після видалення зубів та виконання інших хірургічних втручань, особливо погіршуються процеси регене-рації тканин [4,5].…”
unclassified